Effect of age on pelvic inflammatory disease in nulliparous women using a copper 7 intrauterine contraceptive device. - Booth, M; Beral, V; Guillebaud, J (1980)
Factors affecting the incidence of pelvic inflammatory disease (PID) in a sample of nulliparous women are tabulated and reported briefly. Life-table analyses were used to calculate net rates for the first segment of IUD use. 871 women were inserted with Copper 7 devices in a 30-month period. The disease was diagnosed in 54 women during the 30 months after insertion, and the disease incidence was highest during the first 6 months (3.4 per 100 women); the rate then fell progressively in each successive 6-month period (2, 1.3, .7, and .4 per 100 women). This trend is statistically significant (P .01). Also, the risk of developing the disease was strongly related to age. Cumulative rates were always higher in the younger women at every time interval and decreased as age increased (P .01). Other predisposing factors discovered, besides age, included a history of previous PID (6%), a history of abortion (6%), and a difficult IUD insertion (11%). But the respective rates in women without the disease were not significantly different from those with PID (3, 20, and 9%, respectively). This study cautions young, nulliparous women when choosing IUD contraception because of the infertility likely to result from contracting PID.